Hubungan Obesitas dengan Tingkat Keparahan COVID-19 - Shally G. C. P. Lahagina; Mayer F. Wowor; Siemona L. E. Berhimpon (Medical Scope Journal, 2023)
Abstract: Coronavirus disease 2019 (COVID-19) is an acute respiratory disease caused by infection of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) virus. Obesity is one of the risk factors that might increase the severity of COVID-19 due to anatomical and physiological changes in the body. Previous studies have shown high mortality and morbidity rates in obese patients with COVID-19. This study aimed to evaluate the association between obesity and the severity of COVID-19. This was a literature review study. The results obtained 17 articles concluding that there was an association between obesity and the severity of the disease, however, one article concluded no association between them. The reported severity criteria ranged from severe to critical ill. In conclusion, obese patients with had higher risk to suffer form more severe COVID-19. The outcomes of obese patients with COVID-19 are hospitalization, admission at Intensive Care Unit, intubation, and death. Keywords: COVID-19; obesity; disease severity   Abstrak: Coronavirus Disease 2019 (COVID-19) merupakan penyakit pernapasan akut yang disebabkan oleh infeksi virus Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Obesitas merupakan salah satu faktor risiko yang dapat meningkatkan keparahan COVID-19 terkait adanya perubahan anatomi dan fisiologis tubuh. Hasil penelitian sebelumnya menunjukkan angka mortalitas dan morbiditas yang tinggi pada pasien obesitas dengan COVID-19. Penelitian ini bertujuan untuk mengetahui lebih lanjut mengenai hubungan obesitas dengan tingkat keparahan penyakit pada COVID-19. Jenis penelitian ialah suatu literature review. Hasil penelitian mendapatkan 17 artikel yang menyimpulkan adanya hubungan obesitas dengan tingkat keparahan penyakit pada COVID-19 dan satu artikel menyimpulkan tidak terdapat hubungan obesitas dengan tingkat keparahan penyakit pada COVID-19. Kriteria tingkat keparahan yang dilaporkan mulai dari berat sampai kritis. Simpulan penelitian ini ialah pasien obesitas dengan COVID-19 berisiko lebih tinggi untuk mengalami keparahan penyakit. Luaran pasien dengan obesitas yaitu dirawat inap, menerima perawatan di Intensive Care Unit, diintubasi, dan kematian. Kata kunci: COVID-19; obesitas; tingkat keparahan penyakit